Determinants of Sanitation and Hygiene Status Among Food Establishments in Addis Ababa, Ethiopia - Aderajew Mekonnen Girmay; Sirak Robele Gari; Bezatu Mengistie Alemu; Martin R Evans; Azage Gebreyohannes Gebremariam (SAGE Publishing, 2020)
Introduction: Despite advancements in food science and technology, foodborne disease remains one of the major public health problems. Poor sanitation and hygiene conditions of food establishments are the major causes for the occurrence of foodborne disease. Therefore, this study aimed to investigate core determinants of sanitation and hygiene status among food establishments. Methods: Institution-based cross-sectional study design was conducted in Addis Ababa city. A stratified random sampling technique was deployed to select 413 study participants. Data were collected through interview and using observational checklist. Sample size was determined by using a single population proportion formula. To analyze the data, binary logistic regression and multivariable logistic regression analysis was conducted. In all analysis, P -value less than .05 were considered statistically significant. Results: The study revealed that 57.4% of the food establishments were under poor sanitation status. In the multivariable analysis, presence of trained managers on hygiene and sanitation (adjusted odds ratio [AOR] = 6.10 with 95% confidence interval [CI]: 2.41-15.45), presence of renewed licenses (AOR = 3.07 with 95% CI: 1.18-7.99), absence of bureaucratic function to obtain permission to renew the food establishment buildings (AOR = 2.43 with 95% CI: 1.25-4.70), and presence of at least 10-m distance between toilet and kitchen (AOR = 9.19, at 95% CI: 5.63-15.02) were associated significantly with sanitation and hygiene status. Conclusions: Above average of the food establishments were found to be in poor sanitation and hygiene state. Many core determinant factors that influence sanitation and hygienic status of food establishments were identified. The researchers suggest that formal training on sanitation and hygiene for managers of food establishments should be provided to reduce the occurrence of foodborne diseases. Moreover, strong food and water safety policy and strategy should be promulgated to improve sanitation and hygiene status of food establishments.